1990
DOI: 10.1007/bf00280371
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of the arginine deiminase gene from Mycoplasma arginini

Abstract: Arginine deiminase from Mycoplasma arginini was purified. The purified enzyme has a molecular weight of 46,000 daltons as determined by sodium dodecyl sulfate polyacrylamide gel electrophoresis. Its specific activity (20 units/mg protein) and amino acid composition showed a strong similarity to that of the Mycoplasma arthritidis arginine deiminase. The amino acid sequences of the N-terminal region and three internal peptides generated by enzymatic cleavage of the purified protein were determined. Using a synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In the protein sequence databases, three ADIs were found. The similarities of the ADIs of P. aeruginosa (1), Mycobacterium arginini (27,32), and Mycoplasma hominis (24) to the deduced halobacterial protein are 14.1, 14.0, and 13.4%, respectively. The sequence identities of the putative halobacterial ADI and the bacterial enzymes are much lower than those that have been found for cOTCase and CK (see above).…”
Section: Resultsmentioning
confidence: 99%
“…In the protein sequence databases, three ADIs were found. The similarities of the ADIs of P. aeruginosa (1), Mycobacterium arginini (27,32), and Mycoplasma hominis (24) to the deduced halobacterial protein are 14.1, 14.0, and 13.4%, respectively. The sequence identities of the putative halobacterial ADI and the bacterial enzymes are much lower than those that have been found for cOTCase and CK (see above).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple-sequence alignments of the M. pneumoniae proteins ArcA (Mpn304, Mpn305, and Mpn560), ArcB (Mpn306), and ArcC (Mpn307) with the functional orthologous proteins from M. fermentans (10), M. penetrans (21), M. arginini (22,23), M. hominis (24), and Pseudomonas aeruginosa (25,26) revealed that key amino acids located at specific protein positions and essential for enzymatic activity were not conserved in M. pneumoniae. It was obvious for MPN_304 and MPN_305, because these genes are truncated and encode either only the N-terminal region (MPN_304) or the C-terminal region (MPN_305) of ArcA, and also for MPN_306, which encodes only a truncated ArcB of which the first 70 N-terminal amino acids are missing (5).…”
Section: Resultsmentioning
confidence: 99%
“…The similarity with P. aeruginosa (22) and M. hominis (21) was 49 and 46%, respectively. It seems that within species the sequences are well conserved, for example there is 82% similarity between the M. arginini (18) and M. hominis (21) sequences. However, when comparing sequences between species, the similarity is markedly reduced, with 54% similarity between the M. arginini (18) and P. aeruginosa (22) deiminases for example.…”
Section: Discussionmentioning
confidence: 99%